Breaking the silences, breaking the frames: a gendered diasporic analysis of sexual violence in the DRC. - Godin, Marie (Journal of Ethnic & Migration Studies, 2018)
The role of diasporas in fuelling conflict has been extensively studied, with much less attention being paid to their role in peace-building. It is increasingly recognised that diasporas from conflict regions are contributing to the reconstruction of their countries of origin, acting as ‘peace-makers’ rather than ‘peace-wreckers’. Women and men migrants have also been found to engage differently towards their country of origin, but attention to women’s activism is still scarce. This article addresses the issue of political activism by Congolese women in the diaspora in both the UK and Belgium. Their activities are assessed analytically through the prism of ‘mechanisms of framing’, which shape the ways in which messages are conveyed during the mobilisation process. The paper discusses diagnostic, motivational and prognostic frames to address sexual and gender-based violence against Congolese women in the protracted conflict in the Democratic Republic of the Congo. Framing strategies vary among Congolese diaspora women’s groups depending on the national context in which they are embedded (Belgium and the UK) but a variety of narratives is also discerned which transcends and is shared among Congolese women beyond national borders.